COVID-19 Responses of South Korea as Hybrids of Governance Modes - Lee, Sora; Wong, Ryan (Frontiers in Public Health, 2021)
The countries worldwide have adapted diverse governance approaches to the pandemic to suit their contexts. While the diversity of the country-specific governance responses have been widely discussed, the hybrid nature of those governance practices has been less explored. The paper analyses the responses toward COVID-19 in South Korea as responsive dialogues of different modes of governance, i.e. consensus-based hierarchy, state-sponsored market, and principle-based network. The study aims to remind us that pandemic governance needs to enable organic and responsive processes for all actors in society. The pandemic allowed the emergence of the hybrid of governance modes to cope better with complex realities of the diverse sectors and actors in South Korea The characteristic of the responses diverge from the conventional governance classification of or market-based. It is a responsive and evolving dialogue of different modes of governance, i.e. consensus-based hierarchy, state-sponsored market, and principle-based network. It would be productive to think beyond the oversimplified understandings of governance modes and embrace flexible and different hybrids of governance modes to be more responsive, effective, efficient, and equitable.